Complementary Ion Beam Analysis and Raman Studies for Investigation of the Carbon Coating Impact on Li Insertion/Deinsertion Process at LiFePO4/C Electrodes. Issue 14 (1st January 2017) - Surblé, Suzy; Habrioux, Aurélien; Paireau, Cyril; Berger, Pascal; Khodja, Hicham; Neff, Delphine; Gosset, Dominique; Mailley, Sophie; Patoux, Sébastien
Abstract : Electrode materials were prepared using two commercial C-LiFePO4 powders (called hereafter LFP-A and LFP-B). The nature and the thickness of carbon coating have been characterized by Raman spectroscopy and Transmission Electron Microscopy. The carbon coating of the LFP-B is more graphitized than LFP-A, which appears amorphous. The lithium distribution of these electrodes is investigated using ion beam techniques as a function of its state of charge (SOC). The nuclear microanalyses reveal the presence of different dopings in the active materials (Ti or V). A layer richer in carbon (in addition to the composite electrode) is systematically observed on LFP-A pristine and cycled electrodes. In both materials, immobilization of lithium is visible. Higher content of lithium was observed for the LFP-B electrode.